Pile driving formulas based on pile wave equation analyses - Salgado, Rodrigo; Zhang, Yanbei; Abou-Jaoude, Grace; Loukidis, Dimitrios; Bisht, Vibhav (Computers and geotechnics, 2017)
Pile driving formulas, which directly relate the pile set resulting from a hammer blow to the static load capacity of the pile, are often used to decide whether a pile will have the required design capacity. However, existing formulas do not consider soil or pile type, and do not, in general, reliably predict pile capacity. In this paper, an advanced model for dynamic pile driving analysis was used to develop accurate pile driving formulas. The proposed driving formulas are validated through well-documented case histories. Comparisons of predictions from the proposed formulas with results from static and dynamic load tests show that they produce reasonably accurate predictions of pile capacity based on pile set observations.